Public Deliberation and Social Justice Sensibilities in Greensboro Participatory Budgeting - Russell, Vincent; Jovanovic, Spoma (Communication and Critical/Cultural Studies, 2020)
Participatory budgeting (PB) has emerged as a tool for empowering marginalized communities and advancing social justice concerns through public deliberation and advocacy. However, public deliberation scholars have contested the appropriate roles of social justice, activism, and equity. PB offers a unique site that bridges both deliberation and advocacy, equity, and equality, as it strives to accomplish social change. We detail how the first cycle of Greensboro PB navigated tensions between residents who sought social change and government officials who wished to maintain the status quo. Our communication activism and ethnographic analysis revealed conflicts about voting age and project eligibility, and it demonstrated how government officials dismissed the a narrative of social justice concerns advanced by community members. We argue PB is an example of a public deliberation process that fosters social justice sensibilities among participants and conclude with applied recommendations for design improvements.